Controlled Tautomeric Switching in Azonaphthols Tuned by Substituents on the Phenyl Ring. Issue 3 (8th December 2014) - Antonov, Liudmil; Deneva, Vera; Simeonov, Svilen; Kurteva, Vanya; Crochet, Aurelien; Fromm, Katharina M.; Shivachev, Boris; Nikolova, Rositsa; Savarese, Marika; Adamo, Carlo
Abstract A series of new tautomeric azonaphthols are synthesized and the possibilities for molecular switching are investigated using molecular spectroscopy, X‐ray analysis and density functional theory quantum chemical calculations. Two opposite effects that influence switching are studied: attaching a piperidine sidearm, and adding substituents to the phenyl ring. On the one hand, the attached piperidine moiety stabilizes the enol form leading to a controlled shift of the equilibrium upon protonation. On the other hand, the relative stability of the azonaphthol tautomers strongly depends on the effects of the substituents on the phenyl ring: electron donors tend to stabilize the enol tautomer, whereas electron acceptors lead to stabilization of the keto form. However, these effects do not shift fully the equilibrium towards either of the tautomers. Nevertheless, the effect of the substituents can be an additional tool to affect the switching between "on" and "off" states. Electron‐withdrawing substituents stabilize the keto form and impede switching to the off state, whereas electron donors stabilize the enol form. The effect of the piperidine unit is dominant overall, and with strongly electron‐withdrawing substituents at the phenyl ring, the enol form exists as a zwitterion.